2003
DOI: 10.1021/om0340490
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study on Dimerizations of Phospholes

Abstract: Dimerization reactions through [4 + 2] cycloadditions on 1H-, 2H-, and 3H-phospholes and cyclopentadiene were examined at the B3LYP level using 6-31G* and 6-311+G** basis sets. Activation energies for all the structures indicate that endo transition states are lower by about 1−4.5 kcal/mol compared to the corresponding exo transition states. While the transition-state stabilizations are controlled by secondary orbital interactions, the dimer stabilities are controlled by a mix of secondary orbital interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
2
23
0
1
Order By: Relevance
“…This mechanism has now been studied by the computational approach, which has given support to the concept of the initial double bond rearrangement by the sigmatropic shift mechanism [111]. The trapping of the 2H-phosphole shift product in a DielsAlder reaction has also been examined in this computational study, as well as in another [115,116], giving agreement with the experimental structure Experimentally the Diels-Alder reaction of phospholes with dienophiles gives a 7-phosphanorbornene derivative with endo ring fusion and the P-substituent anti (Section 4). Calculations [60] of the relative energies of the four possible a d d u c t s f r o m m a l e i m i d e a n d 2 , 6 -d iisopropylphenylphosphole, with and without a 3-methyl on the phosphole, showed that the lowest energy product would indeed have the anti, endo structure, as generally observed (Section 4).…”
Section: Computational and Theoretical Studies In Phosphole Chemistrymentioning
confidence: 87%
See 2 more Smart Citations
“…This mechanism has now been studied by the computational approach, which has given support to the concept of the initial double bond rearrangement by the sigmatropic shift mechanism [111]. The trapping of the 2H-phosphole shift product in a DielsAlder reaction has also been examined in this computational study, as well as in another [115,116], giving agreement with the experimental structure Experimentally the Diels-Alder reaction of phospholes with dienophiles gives a 7-phosphanorbornene derivative with endo ring fusion and the P-substituent anti (Section 4). Calculations [60] of the relative energies of the four possible a d d u c t s f r o m m a l e i m i d e a n d 2 , 6 -d iisopropylphenylphosphole, with and without a 3-methyl on the phosphole, showed that the lowest energy product would indeed have the anti, endo structure, as generally observed (Section 4).…”
Section: Computational and Theoretical Studies In Phosphole Chemistrymentioning
confidence: 87%
“…An important feature of 113 is that there are trimethylsilyl groups present at the 2,5-positions; they play a useful role, since the silyl groups can be transferred to the carboxylate ions formed at these positions to generate a new phospholide (114). After one carboxylate has been attached to the 2-position, a second series of reactions occurs to attach a carboxylate to the 5-position (115). The sequence of reactions for achieving the mono-carboxylate 114 is shown in Equation 38; the same reactions then lead to the di-carboxylate (115).…”
Section: Reactions At the Phosphole Double Bonds And Syntheses Based mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 a shows a model contour plot of a PES with two competing cycloaddition transition states, TS a and TS b, a second-order saddle point (SOSP) that connects them, and the Cope TS (TS c), corresponding to isomerization of the cycloadducts. In the diene dimerizations studied by Caramella and others, [55] TS a and TS b have merged into a single "bis-pericyclic" transition state, TS1 (Figure 6 b). On such a surface, the second-order saddle point is lost and a VRI point intervenes between the bis-pericyclic TS and the Cope transition state, TS2.…”
Section: Cycloadditionsmentioning
confidence: 90%
“…808 Dimerisation of 1H-, 2H-and 3H-phospholes through [4þ2] cycloaddition reactions have been studied by density functional theory, and compared to the related dimerisation of cyclopentadiene. 809 Treatment of the [4þ2]-dimer (289) of 2,5-diphenyl-5H-phosphole with iodomethane gives a monophosphonium salt, which, with thallous ethoxide, is converted into the new chelating bis(phospholene), (290) via cleavage of the P-P bond. 810 New tricyclic phosphines, e.g., (291), have been obtained via intramolecular Diels-Alder reactions of phospholes bearing an allyloxy, allylamino or 3-buten-1-yl substituent at phosphorus.…”
Section: Phosphirenes Phospholes and Phosphininesmentioning
confidence: 99%